Use of appreciatives in five migrant groups: local adequacy and global prestige - Manjón-Cabeza Cruz, Antonio; Oyono Midje, Esther (Círculo de Lingüística Aplicada a la Comunicación, 2022)
In the process of linguistic adaptation of migrants, it may happen that they find themselves in a context where the forms mostly used by their neighbours do not coincide with those used in the prestigious varieties. This is the case of the diminutive appreciative suffixes in Granada, where, as a peculiarity in the Hispanic world, three productive suffixes are used: ‑illo, -ito and -ico. We study the processes of accommodation in the use and learning of diminutives in five migrant groups. Two of them are Spanish-speaking: Ecuadorians and Equatoguineans, while the remaining three are not originally Spanish-speaking: Poles, Romanians and Moroccans. The results point to a rejection of the more local suffix (-ico) and alternation between -illo and -ito, but, unlike the people of Granada, -ito is the most frequently used suffix.
Keywords: migrants; adequacy; diminutives; Granada